Experience in Cryopreserved Placenta Application When Treating Fetoplacental Failure and Fetus Hypoxia - Kuzmina, I. Yu.; Chadayev, V. Ye.; Prokopyuk, O. S.; Karpenko, V. G. (Problems of Cryobiology and Cryomedicine, 2006)
The data about accumulated experience in application of cryopreserved placenta in obstetrics, aimed to treating fetoplacental failure (FPF) and chronic fetal hypoxia (CFH) are shown. The effect mechanism of cryopreserved placenta is based on the effect of metabolically active substances of placental origin on different organs and systems of an organism. The implantation of cryopreserved placenta fragment (CPF) considerably improves placenta echostructure of a recipient, enriches uterus-fetus-placenta blood flow due to remodulating placental vessel channel, results in blood redistribution in placental structures, normalises a synthesis of placental proteins in pregnant woman’s organism. The introduction in FPF and CFH therapy protocol of subcutaneous CPF implantation augments the treatment efficiency for this pathology, favourably affects the labour outcome.